NAP modulates hyperglycemic–inflammatory event of diabetic retina by counteracting outer blood retinal barrier damage. Issue 4 (30th October 2018) - D'Amico, Agata Grazia; Maugeri, Grazia; Rasà, Daniela; Federico, Concetta; Saccone, Salvatore; Lazzara, Francesca; Fidilio, Annamaria; Drago, Filippo; Bucolo, Claudio; D'Agata, Velia
Abstract: Diabetic retinopathy (DR) is a common microvascular complication of diabetes. Prolonged hyperglycemia stimulates inflammatory pathway characterized by the release of some cytokines leading to the impairment of blood retinal barrier (BRB). NAP exerts a protective effect in various eye diseases, including DR. So far, the role of NAP in the modulation of inflammatory event during early phase of this pathology has not been investigated yet. In the current study, we have studied the retinal protective effect of NAP, injected into the eye, in diabetic rats. NAP treatment exerts a dual effect downregulating interleukin (IL)‐1β and its related receptors and upregulating IL‐1Ra expression. We have also tested the role of this peptide in human retinal epithelial cells (ARPE19) cultured on a semipermeable support and exposed to hyperglycemic–inflammatory insult, representing a in vitro model of diabetic macular edema, a clinical manifestation of DR. The results have shown that NAP prevents outer BRB impairment by upregulating the tight junctions. In conclusion, deepened characterization of NAP action mechanism on hyperglycemic–inflammatory damage may be useful to develop a new strategy to prevent retinal damage during DR. Abstract : NAP interferes with interleukin (IL)‐1 family member's expression pattern by contributing to maintain outer blood retinal barrier (BRB) integrity. Intraocular administration of NAP induces a significant downregulation of retinal IL‐1β and its related transmembrane receptors in streptozotocin (STZ)‐injected rats. NAP upregulates the levels of both tight junction (TJ)‐related proteins.